Individual and Social-Contextual Factors Underlying Adolescents' Commitment to Victimizing Friendships: A Qualitative Analysis. (January 2021) - Bouchard, Karen; Smith, J. David; Woods, Heather
Previous research indicates that victimized youth are reluctant to address their friends' victimizing behaviors and are likely to remain in a victimizing friendship despite experiencing significant distress. Research investigating the complex factors underlying this commitment to victimizing friendships is required. To this end, a qualitative research design was used as previously victimized youth asynchronously contributed to an anonymous online discussion forum for 2 months. Guided by two theories used to understand staying/leaving processes in intimate partner violence and a social-ecological systems perspective, the data were captured into descriptive categories. The results demonstrate that adolescents ( N = 25) were reluctant to address their friends' victimizing behaviors and many persisted in their victimizing friendships. The factors underlying this reluctance were categorized as cognitive, relational, and contextual. The results indicate that persisting in a friendship despite feeling victimized can seem paradoxical to outsiders but there are clear reasons underlying adolescents' choices.